Does Fetal Fibronectin Predict the Delivery Route in Nulliparous Women at Postterm Induced by Dinoprostone? - Goksever Celik, Hale; Celik, Engin; Yetkin Yildirim, Gonca (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: Digital cervical evaluation has been used to determine the likelihood of vaginal delivery which is considered by many women to be non-tolerable. Recently, alternative approaches such as transperineal ultrasound, fetal fibronectin test in cervicovaginal secretions have been investigating for the prediction of the delivery route. We aimed to study whether the usefulness of qualitative fetal fibronectin test in cervicovaginal secretions for the prediction of vaginal delivery in pregnant women at postterm induced with dinoprostone. Study design: A total of 32 nulliparous pregnant women at postterm were enrolled in this prospective observational study. Fetal fibronectin test was applied to all participated women before the induction with dinoprostone and transvaginal ultrasonography was performed to measure cervical length. Results: The women having positive fetal fibronectin test result gave birth through vaginal route, except one case. Although there is no statistically significant difference, the shorter cervical length was associated with vaginal delivery in our population. Conclusion: Fetal fibronectin test has a predictive value for delivery route in nulliparous women at postterm. Fetal fibronectin test may be used as a “rule out” test because the rate of fetal fibronectin positivity was found to be higher in patients who gave birth via vaginal route. As also shown in our study, although there is no statistically significant difference, the pregnant women with shorter cervical length might have a high possibility to achieve vaginal delivery.